(untitled) (International Journal of Engineering and Computer Science, 2017)
The goal of this project is to design a system that will work on most of smart phones and palms which will be helpful when visiting any new place or cities. This system finds a route using user conditions and criteria . Those above mentioned criteria should be simple and natural, like, for example: a list of museums, the most famous historical objects, , constraints to travel by bus and by walking. The system should find a solution that fulfils those criteria, show it on screen, show names of objects, some short descriptions and photos of them and possible entrance costs.